Pronase hydrolysis as a pretreatment for quantifying Maillard intermediates during toasting of cornflakes - Cueto, Mario Alberto (2016)
Some of the products generated by the Maillard reaction are desired and very important for defining consumer acceptance of breakfast cereals. However, in recent years there has been an increased concern about compounds that are potentially harmful such as furfurals. The aim of this work was to analyze the effectiveness of protein hydrolysis with pronase as a pretreament for the evaluation of furfurals generated by the Maillard reaction during toasting of cornflakes and the parallel development of brown and fluorescent compounds. Furfurals were more accurately quantified with the pronase hydrolysis pretreatment because the protein matrix binds furfurals and fluorescent compounds. For control of the early reaction steps in the toasting process, the most sensitive parameter was fluorescence.